Adolescent occupational injuries requiring hospital emergency department treatment: a nationally representative sample. - Layne, L A (1994)
Data from a nationally representative sample of emergency departments for the 6-month period July through December 1992 were used to examine nonfatal occupational injuries sustained by adolescents aged 14 through 17 years. There were 679 occupational injuries, corresponding to an estimated 37,405 injuries nationwide. Males constituted 65.8% of the injury victims. The injury rate for males was 7.0 per 100 full-time employees, compared with 4.4 for females. Lacerations to the hand or finger accounted for 25.6% of all injuries. The majority of injuries occurred in retail trades (53.7%), which also had the highest rate (6.3 per 100 full-time employees). Seventy-one percent of the injuries in retail trade occurred in eating and drinking establishments.